Fangirling Culture in X: a Virtual Ethnographic Study of Seventeen Boygroup Fans in Makassar City - Nabila Rahmayuni Saharuddin; Abdul Rahman (PT. Gudang Pustaka Cendekia, 2026)
This study explores the cultural practice of fangirling on social media platform X as a space for identity negotiation and communal solidarity in the digital era. Using a digital ethnography approach, data was collected through participant observation, in-depth interviews with fans, and a documentary study of the digital footprints of the informants. The results show that fangirling is not merely a form of passive consumption, but rather a communal cultural activity carried out massively and organized through fictitious kinship structures in cyberspace. This phenomenon manifests itself in the form of digital